2006
DOI: 10.1051/0004-6361:20053854
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an MHD shear flow with a piecewise linear velocity profile

Abstract: In this paper we present the results of the stability analysis of a simple shear flow of an incompressible fluid with a piecewise linear velocity profile in the presence of a magnetic field. In the flow, a finite transitional magnetic-free layer with a linear velocity profile is sandwiched by two semi-infinite regions. One of these regions is magnetic-free and the flow velocity in the region is constant. The other region is magnetic and the fluid in it is quiescent. The magnetic field is constant and parallel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…These results were reconsidered by Ruderman and Brevdo (2006). In accordance with their analysis the transitional layer with a continuous velocity variation at the solar wind side of the heliopause would destabilise the flow.…”
Section: Heliopause Stabilitymentioning
confidence: 90%
“…These results were reconsidered by Ruderman and Brevdo (2006). In accordance with their analysis the transitional layer with a continuous velocity variation at the solar wind side of the heliopause would destabilise the flow.…”
Section: Heliopause Stabilitymentioning
confidence: 90%
“…In a 3D HD simulations by Reyes-Iturbide et al (2019) these features can also be found. A detailed analysis of the KH in the case of the heliosphere is given by Ruderman & Brevdo (2006), where the authors show that the magnetic field stabilizes the astropause. The feature of a smooth astropause is mainly seen in heliospheric simulations (for example Pogorelov et al 2017a) and in the 3D MHD astrosphere simulations by Katushkina et al (2018) and Gvaramadze et al (2018).…”
Section: The Stability Of the Astropause And Shocks In (M)hd Simulationsmentioning
confidence: 99%
“…Observations of periodic motion in the last decade through high resolution space and ground-based telescopes have changed our view about the dynamics of solar plasma in many ways. The observed waves and oscillations are used to describe the stability of the plasma (Ruderman & Brevdo 2006;Simpson, Ruderman & Erdélyi 2006), to tackle the complicated problem of coronal heating and plasma acceleration in the solar wind (Ballai, Thelen & Roberts 2003), to prescribe the dynamical behaviour of various solar structures (see, e.g. De Pontieu, Erdélyi & James 2004;Marcu, Ballai & Pintér 2006) or to sample the magnetic field, both in coronal loops and quiet Sun (Nakariakov et al 1999;Ballai 2007).…”
Section: Introductionmentioning
confidence: 99%